MENINGKATKAN SUMBER DAYA MASYARAKAT MELALUI PENDIDIKAN ISLAM NON-FORMAL - Dicky Setiady; Muhammad Nurhikmah Wiguna (FKIP Universitas Jember, 2022)
Non-formal Islamic education in Indonesia, especially in the Greater Jabodetabek area, has a central role in fostering public education. Education which tends to be free is a source or a solution for equal distribution of education in Indonesia. But apart from its usefulness, when viewed in terms of its contextualization with the times, it seems that this non-formal Islamic education is a little behind by the times. The purpose of this study is to further examine the causes of the lagging behind of non-formal Islamic education, and to seek efforts to improve the non-formal Islamic education system through the role of the academic community. The research method uses a qualitative method with an interview, observation, and questionnaire-based data collection approach. The results of the study show that the cause of the lagging behind of non-formal Islamic education is due to the monotonous curriculum and the lack of support from an economic point of view, causing stagnation of activities in these non-formal educational institutions. Many expectations from the administrators and from the point of view of solution researchers are in the community service program carried out by both lecturers and students to help provide education to non-formal educational institutions so that they are maximally able to play an active role in generating community resources.